PELAYANAN KESEHATAN DI PUSKESMAS BATU AMPAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Saini E.01108128, Yuli (FISIP Universitas Tanjungpura, 2013)
Health services in clinics there are stillÂ some constraints, It has influenced by some factors, the are health Procedure, time and Infrastructure and also the competence official serves. This ministhesis writing is aim to figure out the health services of Batu Ampar local government clinic in Batu Ampar subdistrict and the element that influence it serves. This writing is using Qualitative method with descriptive research. From it we can get the result that is the health services in Batu Ampar local government clinic of Batu Ampar subdistrict of Kubu Raya Regency isnâ€™t maximal. Health is a basic human need, for this healt services should be organized properly.Â key word: Service Health, Local Government Clinic